Legal Protection of Athletes’ Civil Rights in Competitive Sports Activities - Lestari Wulandari S; Ferinandus Leonardo Snanfi; Christine Olidita Indahrami Sanggenafa (Journal of Physical Education Health and Sport, 2025)
The athlete civil protection is a required element in the competitive sport and especially, against contract exploitation, unfair treatment and improper compensation associated to injuries as well as performance success. This paper seeks to evaluate the type of civil law protection that is provided to an athlete in Indonesia and what legal gaps have often been found to exist within the high performance sports. The study focuses on legal documents, regulations, and the contract of the athletes and the cases of the disputes about the bonus claims, the cases of the sponsorship and the end of the training because of the injury using a normative juridical approach and a case study approach. The findings indicate that most of the contracts of athletes have no explicit provisions on health protection, insurance cover, and dispute resolution processes, which expose athletes to unilateral actions by sports organizations. There is also a lack of standardized contract models and a low degree of legal awareness among athletes, especially minors and amateur athletes who start professional careers, which is evidenced. This paper suggests that there should be an expansion of a thorough civil law system of an athlete agreement, which incorporates mandatory insurance, remuneration systems and sporting arbitration as a way of enhancing the legal certainty and just competition in sports.